′Sure closure′-skin stretching system, our clinical experience - Subramania, K I; Mohit, S; Sasidharan, P R; Abraham, M K; Arun, P; Kekatpure, V (Indian Journal of Plastic Surgery, 2005)
Objective: In clinical practice of reconstructive surgery one of the problems one routinely comes across is skin and soft tissue defects, which require coverage. Coverage of such wounds requires primary/secondary closure, skin grafting or flaps. The objective of our clinical series was to assess the efficacy of sure closure skin stretching system for closure of defects which otherwise would have required major flap cover or skin grafting.Methods: Our series included five patients with different causes and types of wound defects namely:1. Post-traumatic soft tissue defect on dorsum of hand.2. Post fasciotomy wound on leg (anterolateral aspect).3. Abdominal wound dehiscence following surgery for enterocutaneous fistula.4. Leg soft tissue defect following dehiscence of fasciocutaneous flap.5. Secondary defect following harvesting a lateral arm/forearm free flap.The device was applied to skin edges after preparing the wound under local anesthesia and the skin edges were brought together by turning the skin-stretching knob. After adequate approximation of the edges of the wound it was sutured by conventional suturing techniques.Results: All the wounds could be successfully closed using the skin stretching system in our series. The time taken for the closure ranged from 2 to 48 h.Conclusions: Sure closure skin stretching system is an effective device for closing some of the skin defects which otherwise would have required skin flaps or grafts. In all the patients wound closure could be achieved by this method and was carried out under local anesthesia. Use of this technique is simple and helps to reduce the morbidity and cost of treatment by allowing the reconstructive surgeon to avoid using major flaps or grafts.
Keywords: Skin defects; Skin closure; Sure closure device